THE ESSENCE AND STRUCTURE OF PERSONAL CREATIVITY - Tairov Ilhom Yorievich (Scholar Express Journal, 2023)
Today, many approaches have been developed to determine the nature of creativity. Therefore, it is impossible to give a single generalizing definition that would satisfy all researchers. Creativity is a property that is actualized only when the environment allows it; it is important for the child that the environment contains samples of creative behavior, its results and subject-information enrichment.
Keywords: creativity; person; factors